EXTENDED ANALYSIS ON RIEMANN-LIOUVILLE FRACTIONAL DIFFERENTIAL EQUATIONS: ANTI-PERIODIC BOUNDARY CONDITIONS OF VARIABLE ORDER - Chou, Dean; Wu, Miin; Mokhtar, Mokhtari; Bouazza, Zoubida; İnç, Mustafa; Souid, Mohammed Said (World Scientific Publ Co Pte Ltd, 2026)
In this study, we deal with the ExUnStSo to a class of Riemann-Liouville fractional differential equations with anti-periodic boundary conditions of variable order (RLFDEAPBCVO) using standard fixed point theorems (SFPT). In addition, the Ulam-Hyers-Rassias stability of the considered problem is investigated. Lastly, the results obtained are supported by an example.
Keywords: Anti-Periodic Boundary Conditions; Variable Order; Stability